An OSINT Approach to Automated Asset Discovery and Monitoring - Pedro Daniel Carvalho de Sousa Rodrigues (2019)
The main objective of this thesis is to improve the efficiency of security operations centersthrough the articulation of different publicly open sources of security related feeds. This ischallenging because of the different abstraction models of the feeds that need to be madecompatible, of the range of control values that each data source can have and that will impactthe security events, and of the scalability of computational and networking resources that arerequired to collect security events.Following the industry standards proposed by the literature (OSCP guide, PTES andOWASP), the detection of hosts and sub-domains using an articulation of several sources isregarded as the first interaction in an engagement. This first interaction often misses somesources that could allow the disclosure of more assets. This became important since networkshave scaled up to the cloud, where IP address range is not owned by the company, andimportant applications are often shared within the same IP, like the example of Virtual Hoststo host several application in the same server.We will focus on the first step of any engagement, the enumeration of the target network.Attackers often use several techniques to enumerate the target to discover vulnerable services.This enumeration could be improved by the addition of several other sources and techniquesthat are often left aside from the literature. Also, by creating an automated process it ispossible for security operation centers to discover these assets and map the applicationsin use to keep track of said vulnerabilities using OSINT techniques and publicly availablesolutions, before the attackers try to exploit the service. This gives a vision of the Internetfacing services often seen by attackers without querying the service directly evading thereforedetection. This research is in frame with the complete engagement process and should beintegrate in already built solutions, therefore the results should be able to connect to additionalapplications in order to reach forward in the engagement process.By addressing these challenges we expect to come in great aid of sysadmin and securityteams, helping them with the task of securing their assets and ensuring security cleanlinessof the enterprise resulting in a better policy compliance without ever connecting to the clienthosts.